Insights into the biology and prevention of tumor metastasis provided by the Nm23 metastasis suppressor gene - Marino, Natascia (Cancer Metastasis Rev, 2012)
Metastatic disease is the major cause of death among cancer patients. A class of genes, named metastasis suppressors, has been described to specifically regulate the metastatic process. The metastasis suppressor genes are downregulated in the metastatic lesion compared to the primary tumor. In this review, we describe the body of research surrounding the first metastasis suppressor identified, Nm23. Nm23 overexpression in aggressive cancer cell lines reduced their metastatic potential in vivo with no significant reduction in primary tumor size. A complex mechanism of anti-metastatic action is unfolding involving several known Nm23 enzymatic activities (nucleotide diphosphate kinase, histidine kinase, and 3′–5′ exonuclease), protein–protein interactions, and downstream gene regulation properties. Translational approaches involving Nm23 have progressed to the clinic. The upregulation of Nm23 expression by medroxyprogesterone acetate has been tested in a phase II trial. Other approaches with significant preclinical success include gene therapy using traditional or nanoparticle delivery, and cell permeable Nm23 protein. Recently, based on the inverse correlation of Nm23 and LPA1 expression, a LPA1 inhibitor has been shown to both inhibit metastasis and induce metastatic dormancy.